The modern approaches to the diagnostics and treatment of Lennox–Gastaut syndrome (literature review) - K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии)
Despite significant advances made in epileptology, treatment-resistant epilepsy accounts for approximately 30 % of all forms of this disease. Such diseases include, among others, Lennox–Gastaut syndrome – a classic developmental and epileptic encephalopathy with onset in childhood, characterized by resistance to therapy, severe course and poor prognosis. For patients in this category, the search for new effective antiepileptic drugs remains highly relevant, especially in cases where numerous combinations of antiepileptic drugs do not produce an effect, surgical treatment is impossible, and alternative methods (vagus nerve stimulation and ketogenic diet) are ineffective. The authors present a review of the literature on the modern definition and diagnostic criteria of Lennox–Gastaut syndrome, diagnostic methods and treatment of this form of epilepsy, which has a severe course and a generally unfavorable prognosis.